The Application of Strategic Competition in EFL Setting in Transactional and Interpersonal Conversation Class - Riana Eka Budiastuti; Testiana Deni Wijayatiningsih (English Language and Literature International Conference (ELLiC) Proceedings, 2022)
This study attempts to describe the communication strategies (CS) utilized by English education students in the first semester at the University of Muhammadiyah Semarang. Data derived from the transcription of online conversation using virtual video conference occurred in the classroom. By evaluating their utterances and applying Celce Murcia (1995) typologies of communication strategies, this descriptive qualitative study was able to determine the frequency of communication methods utilized in the class of Transactional and Interpersonal Conversation. According to the findings, the frequency of communication strategies was Avoidance Strategies (15%), compensatory strategies (48%), Stalling or time gaining strategies including fillers, hesitations, and gambits (16%), and appeal for help (22%).